2016
DOI: 10.1177/0164027516682814
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Types, Health, and Health-Care Use Among South Korean Older Adults

Abstract: This study examines the associations among social network types, multiple health conditions, and various health-care use. Data came from the 2006 and 2008 wave of the Korean Longitudinal Study of Aging. A two-step cluster analytical approach was used to identify social network types. Regression models determined associations between social network types, health changes, and health-care use, including checkups, outpatient service, traditional medicine use, and hospitalization. Four social network types (restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…In this sense, the application of social networks approach in the study of social environments where people live and work is fundamental to understand how interactions, social connectedness, and functions and types of social networks might be critical for health outcomes at different times and ages [27,28]. Some authors have established types of networks based on the characteristics of network composition or types of social support or interaction such as frequency, and these have been related to aspects such as the capacity of interpersonal environments to mobilise and share resources [29], health-related behaviours [30], perceived availability of social support [31] and healthcare usage [32]. The main idea of this approach is that individuals are surrounded by a network of relationships that influence health-related behaviours [33] and help-seeking resources.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the application of social networks approach in the study of social environments where people live and work is fundamental to understand how interactions, social connectedness, and functions and types of social networks might be critical for health outcomes at different times and ages [27,28]. Some authors have established types of networks based on the characteristics of network composition or types of social support or interaction such as frequency, and these have been related to aspects such as the capacity of interpersonal environments to mobilise and share resources [29], health-related behaviours [30], perceived availability of social support [31] and healthcare usage [32]. The main idea of this approach is that individuals are surrounded by a network of relationships that influence health-related behaviours [33] and help-seeking resources.…”
Section: Introductionmentioning
confidence: 99%
“…As income increased, the use of health services increased and vice versa. This relationship was also true based on satisfaction with economic status, household assets, individual wealth, household expenses, monthly and annual household income [5,17,25,30,31,37,39,43,47,52,53,58,59,61]. Regarding employment status, retired and unemployed elderly people used less health services than employed elderly people [3,12,64].…”
Section: Resultsmentioning
confidence: 87%
“…Andersen's behavioral model of health service utilization was used as a theoretical framework to classify the Results of this study into three categories: Predisposing factors (Age, gender, marital status, ethnicity), Enabling factors (Education level, employment status, income level, insurance coverage, social network, social support, place of residence) and Need factors (Having a chronic disease, self-assessed health status, need for health care services, severity of the disease, number of diseases, comorbid diseases, type and duration of disease, having disability or functional limitation, unhealthy lifestyle). Findings of the reviewed articles showed that with the increase of age, the need to use health services increases [3,15,25,33,37,39,40,43,50,53,54,56,59], but in some studies, with increasing age and exceeding 85 years, the use of health services decreased [55,58,61]. Gender was associated with access to health services such that women were significantly more likely to seek health services [5,9,15,17,25,30,39,43,45,49,50,52,53,54,58,59,61,64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These people will interact continuously to discuss and resolve any matters related to the elderly at the centers; thus, an effective support system and conducive environment would be significant to improve the health and happiness of the elderly. Hence, their knowledge and skills in health care will help them to provide better services to elderly, and also help them to be more knowledgeable and skilled health care practitioners, needed for the health promotion and education of elderly care to the public (World Health Organization, 2016;Park et al, 2018). More importantly, the well-developed aging care centers and skilled operators that have the right attitude and adequate knowledge on providing the individual care to the elderly are required in the aging care services.…”
Section: Introductionmentioning
confidence: 99%